Protein growth factors and myocardial remodeling in hypertension in men with psoriasis - V. A. Razin; Yu. N. Kurganova; A. S. Nesterov; I. M. Vorotnikov (Лечащий Врач, 2024)
Background. Protein growth factors such as vascular endothelial growth factor and insulin-like growth factor are involved in the pathogenesis of hypertension and psoriasis, and endothelial dysfunction is also noted in these diseases. Despite extensive studies of these nosologies, there is still insufficient information about the nature of remodeling of the cardiovascular system in the case of a combination of these pathologies.Objective. The aim of the study was to study the content of circulating growth factors — vascular endothelial growth factor, insulin-like growth factor, and compare myocardial remodeling in hypertension in men with and without psoriasis.Materials and methods. 165 male patients who were on outpatient treatment for stage 2 hypertension, average age 53,1 ± 7,2 years, were studied. The patients were divided into 2 groups: group 1 (comparison group) of 80 patients with hypertension, group 2 (main group) of 85 patients with hypertension with psoriasis vulgaris. Plasma concentrations of growth factors were assessed in all patients and echocardiography was performed. In the group of patients with hypertension and psoriasis, the level of vascular endothelial growth factor (p = 0,0002) and insulin-like growth factor (p = 0,0001) is higher than in patients with hypertension without psoriasis.Results. It was revealed that in patients with a combination of arterial hypertension and psoriasis, the left ventricular myocardial mass index (145,2 ± 21,4 g/m2) was significantly higher (p = 0.041) than in patients with arterial hypertension. In patients with arterial hypertension and psoriasis, concentric hypertrophy of the left ventricle was significantly more common (χ2 = 4,27, p = 0,039).